Synthesis and pharmacological evaluation of conformationally restricted κ-opioid receptor agonists12. Issue 12 (17th October 2016) - Wenker, Yvonne; Soeberdt, Michael; Daniliuc, Constantin; Ständer, Sonja; Schepmann, Dirk; Wünsch, Bernhard
Abstract : Additional N- and O-atoms in the bicyclic scaffold increase polarity and allow fine tuning of pharmacodynamic and pharmacokinetic properties of novel κ agonists. Abstract : In order to obtain novel polar κ agonists the κ-pharmacophoric ethylenediamine structural element was embedded in a rigid bicyclic scaffold. The pyridooxazine system was selected since it contains polar O- and N-atoms in the 1- and 7-positions, respectively. An axially oriented pyrrolidine ring was attached at the 5-position and the dichlorophenylacetyl moiety was introduced at N-4. The key steps of the 11-step synthesis are a double Henry reaction of iminodiacetaldehyde7 with nitromethane and the introduction of the azido moiety of13 by Mitsunobu reaction of the alcohol11 with Zn(N3 )2 ·(pyridine)2 . The X-ray crystal structure analysis of17b shows a dihedral angle N(acyl)-C-C-N(pyrrolidine) of −60.8(2)°, which is close to the postulated optimal angle. Moderate κ affinity was found for the secondary amine17a ( K i = 132 nM) and the methyl derivative17b ( K i = 266 nM). In the [ 35 S]GTPγS assay the secondary amine17a showed 28% agonistic activity compared to U-69, 593. Although17a and17b contain all crucial κ-pharmacophoric elements, their κ affinity is rather low, which might be attributed to the unfavorable cis -orientation of the pyrrolidine ring and the dichlorophenylacetamido moiety and/or the additional O- and N-atoms in the 1- and 7-positions.